2016
DOI: 10.1016/j.rboe.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between peri-incisional dysesthesia and the vertical and oblique incisions on the hamstrings harvest in anterior cruciate ligament reconstruction

Abstract: ObjectiveTo compare the incidence of peri-incisional dysesthesia according to the skin incision technique for hamstring tendon graft harvest in anterior cruciate ligament reconstruction.MethodsThirty-three patients with ACL rupture were separated in two groups: group 1, with 19 patients submitted to the oblique skin incision to access the hamstrings and group 2–14 patients operated by vertical skin incision technique. The selected patients were assessed after surgery. Demographic data and prevalence of dysesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The clinical IPBSN deficit was defined as “hypoesthesia”, “dysesthesia” or “sensory disturbance”. Evaluations were performed using light touch [10, 13, 16], palpation [22], pin prick [25] or blunt needle [28]. One study used patient self‐assessment of the IPBSN injury [17] and one study performed an instrumental evaluation of IPBSN deficit with an electrophysiological study of sensory nerve potentials [30] (Tables 1, 2, 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The clinical IPBSN deficit was defined as “hypoesthesia”, “dysesthesia” or “sensory disturbance”. Evaluations were performed using light touch [10, 13, 16], palpation [22], pin prick [25] or blunt needle [28]. One study used patient self‐assessment of the IPBSN injury [17] and one study performed an instrumental evaluation of IPBSN deficit with an electrophysiological study of sensory nerve potentials [30] (Tables 1, 2, 3).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [13, 16, 30] did not report significant differences between the two incisions, three studies [17, 25, 28] reported a significantly higher incidence of IPBSN injury in the case of vertical incision and one study [10] did not perform a statistical analysis that was sufficient in order to draw conclusions. When a fixed‐effect meta‐analysis of the three RCTs was performed, a significant RR of 2.39 ( p < 0.0001) was reported when a vertical incision was performed (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 Several investigations suggest the utilization of horizontal and oblique incisions to expose and harvest the tibial insertion of the hamstring tendons to reduce the damage to the IPBSN compared with vertical incisions; however, there is no consensus so far. 4,8 It has been articulated that the incisions with greater respect to the anatomy of the IPBSN could guarantee a lower complication rate. Subsequently, the present study aimed to compare the incidence of IPBSN injury between two different incisions, vertical and oblique, used for hamstring tendon graft harvest.…”
Section: Introductionmentioning
confidence: 99%